Documenting Nigeria’s Hip Hop Music Evolution in Nollywood: an Examination of Tunde Kelani’s Campus Queen (American Journal of Interdisciplinary Research and Innovation, 2022)
It has been established that the Nigerian music industry has grown tremendously in recent times through the popularity and dynamism of the Hip hop genre, which has positioned itself as the mainstream music presently. Likewise the Nigerian film industry now referred to as Nollywood is credited as the fastest growing film industry and rated the third largest film industry in the world after Hollywood and India’s Bollywood and currently accounts for an estimated N 853.9 billion ($7.2 billion)  or 1.42 percent of Nigeria's GDP. This paper establishes the interface between popular music culture (hip hop) and Nollywood through the notion of documentation with a highlight of how Hip hop music is being documented in Nollywood formative years either consciously or un-consciously. The paper adopts a qualitative research method with an in-depth analysis of music in the movie-Campus Queen.